Targeted transgene insertion into the CHO cell genome using Cre recombinase‐incorporating integrase‐defective retroviral vectors. Issue 7 (7th February 2016) - Kawabe, Yoshinori; Shimomura, Takuya; Huang, Shuohao; Imanishi, Suguru; Ito, Akira; Kamihira, Masamichi
ABSTRACT: Retroviral vectors have served as efficient gene delivery tools in various biotechnology fields. However, viral DNA is randomly inserted into the genome, which can cause problems, such as insertional mutagenesis and gene silencing. Previously, we reported a site‐specific gene integration system, in which a transgene is integrated into a predetermined chromosomal locus of Chinese hamster ovary (CHO) cells using integrase‐defective retroviral vectors (IDRVs) and Cre recombinase. In this system, a Cre expression plasmid is transfected into founder cells before retroviral transduction. In practical applications of site‐specific gene modification such as for hard‐to‐transfect cells or for in vivo gene delivery, both the transgene and the Cre protein into retroviral virions should be encapsulate. Here, we generated novel hybrid IDRVs in which viral genome and enzymatically active Cre can be delivered (Cre‐IDRVs). Cre‐IDRVs encoding marker genes, neomycin resistance and enhanced green fluorescent protein (EGFP), flanked by wild‐type and mutated loxP sites were produced using an expression plasmid for a chimeric protein of Cre and retroviral gag‐pol. After analyzing the incorporation of the Cre protein into retroviral virions by Western blotting, the Cre‐IDRV was infected into founder CHO cells, in which marker genes (hygromycin resistance and red fluorescent protein) flanked with corresponding loxP sites are introduced into the genome. G418‐resistant colonies expressing GFP appeared and the site‐specific integration of the transgene into the expected chromosomal site was confirmed by PCR and sequencing of amplicons. Moreover, when Cre‐IDRV carried a gene expression unit for a recombinant antibody, the recombinant cells in which the antibody expression cassette was integrated in a site‐specific manner were generated and the cells produced the recombinant antibody. This method may provide a promising tool to perform site‐specific gene modification according to Cre‐based cell engineering. Biotechnol. Bioeng. 2016;113: 1600–1610. © 2016 Wiley Periodicals, Inc. Abstract : Viral genome and enzymatically active Cre recombinase were encapsulated into viral virions of an integrase‐defective retroviral vector (Cre‐IDRV). Cre‐IDRV enabled targeted transgene insertion into a pre‐determined chromosomal locus of CHO cells, by the recombinase‐mediated cassette exchange.